362 Epidemiologic concerns regarding denominator selection for sports injury studies. (3rd March 2020) - Swedler, David; Baker, Charlotte; Kerr, Zachery; Liller, Karen; Janosky, Joseph; Dunya, Bayat; Simmons, Molly; Wasserman, Erin; Schaffer, Katie
Abstract : Background: To compare populations and maximize generalizability, epidemiologists must accurately assess and describe the time-at-risk for a given population. In sports injury research and surveillance, public health researchers and practitioners must identify denominators across sports with hazards of varying severity when attempting to situate risk for injuries. A problem arises, however, when time or population at risk cannot be collected for a given group, or are not applicable across different sports. Objective: Describe the denominators used in sports injury surveillance and research, and evaluate their strengths and weaknesses. Assess the appropriateness of given exposure measures for specific risk assessments. Propose next steps for more accurately measuring exposure within and across sports, considering each measurement within the context of real-world constraints. Design: A literature review identified athlete-exposures (AEs), playing time, athlete-participation, cumulative incidence, census population data, and other measures of exposure in the peer-reviewed and gray literature. All denominators were placed into a matrix to describe strengths, weaknesses, opportunities for generalizability, and threats to validity. We describe measurement precision and public health applicability for each. Patients (or Participants): Sports and recreation participants of any age in peer-reviewed sports-injury surveillance and injury intervention articles. Interventions (or assessment of risk factors): Risk factors include the injury denominator used, denominator quality, and how the authors utilized the data collected. Main outcome measurements: Outcome measurements include athlete-exposure, time-at-risk, and population. Results: Playing time and movement tracking provide the most precision for exposure while the athlete-exposure has the broadest generalizability across sports and across levels within a given sport. Further development of an AE-by-position or time-by-position matrix may increase precision of measurement within sports. Conclusions: Further development of positional exposure helps create generalizability within and between sports injury studies. This study will provide assistance to researchers and practitioners when identifying the appropriate measures for their population-at-risk.